Propagation effects in highly ionised gas media. (April 2016) - Tosa, V.; Kovács, K.; Major, B.; Balogh, E.; Varjú, K.
Abstract: The problem of propagation of an ultraintense pulse in a gas medium is solved by using a 3D nonadiabatic model extended to the case of multiple ionisation of atoms in the interaction region. A complex space – time coupling of the pulse during its propagation and strong spatial and temporal changes in the field distribution are shown.